Farmers’ perceptions of learning through dairy producer organizations in Colombia - Ramírez-Gómez, Carlos Julián; Patiño-Murillo , Marcela; Pelegrina, Juliano (Revista de Ciências Agroveterinárias, 2024)
The dairy sector is of great relevance for the rural economy in countries like Colombia, but at the same time it faces great challenges related to international trade dynamics. To seek to strengthen the production link in the chain, various rural extension programs have emerged for this purpose. However, within the framework of dairy farmer social learning, challenges still remain related to the best ways to promote learning. Therefore, in this study we asked ourselves if interactions directly between two dairy producer organizations could have positive influences on people. Therefore, this study aims to carry out a qualitative evaluation of learning perceptions among milk producers in the Department of Caldas, based on territorial guided tours with a focus on interaction between producer organizations in the sector. In this sense, 10 dairy producer organizations were taken who were in search of strengthening, and guided tours were carried out to other rural territories with five outstanding dairy organizations recognized for their capabilities and innovations. After that, 81 interviews were carried out with volunteer producers from all the visiting associations. The evaluation of learning perceptions after the guided tours with associations that are recognized in other territories had a positive influence on the producers. The greatest thematic learning interest focused on the associative and organizational issues of the visited reference, followed by technological aspects used at the level of the milk producing farm, and finally the role of the family in the context of production. Furthermore, the issues related to collection, transformation and marketing were the least relevant.